Physical exercise and the functions of microRNAs - Santos, João Antonio Celestino dos [UNESP] (2022)
MicroRNAs (miRNAs) control RNA translation and are a class of small, tissue-specific, non-protein-coding RNAs that maintain cellular homeostasis through negative gene regulation. Maintenance of the physiological environment depends on the proper control of miRNA expression, as these molecules influence almost all genetic pathways, from the cell cycle checkpoint to cell proliferation and apoptosis, with a wide range of target genes. Dysregulation of the expression of miRNAs is correlated with several types of diseases, acting as regulators of cardiovascular functions, myogenesis, adipogenesis, osteogenesis, hepatic lipogenesis, and important brain functions. miRNAs can be modulated by environmental factors or external stimuli, such as physical exercise, and can eventually induce specific and adjusted changes in the transcriptional response. Physical exercise is used as a preventive and non-pharmacological treatment for many diseases. It is well established that physical exercise promotes various benefits in the human body such as muscle hypertrophy, mental health improvement, cellular apoptosis, weight loss, and inhibition of cell proliferation. This review highlights the current knowledge on the main miRNAs altered by exercise in the skeletal muscle, cardiac muscle, bone, adipose tissue, liver, brain, and body fluids. In addition, knowing the modifications induced by miRNAs and relating them to the results of prescribed physical exercise with different protocols and intensities can serve as markers of physical adaptation to training and responses to the effects of physical exercise for some types of chronic diseases. This narrative review consists of randomized exercise training experiments with humans and/or animals, combined with analyses of miRNA modulation.